1999
DOI: 10.1002/(sici)1520-667x(1999)11:4<305::aid-mcs8>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and stationary phase selectivity in capillary electrochromatography method development: Comparison of C18, C8, and phenyl‐bonded phases for the separation of a series of substituted barbiturates

Abstract: Abstract:The capillary electrochromatographic separation of six substituted barbiturates in the ion-suppressed mode was investigated on commercially available C18, C8, and, phenyl-bonded packing materials. The effect on the retention behavior of mobile phase composition, buffer pH, buffer ionic strength, and temperature was studied. Successful chromatography of the barbiturates was achieved with all three packing materials over a pH range from 2.3 to 7.8. It was Ž . notable that a significant electroosmotic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On the other hand, in CEC with ODS (Hypersil C 18 ), Euerby et al [12] demonstrated that the elution order of studied barbiturates was completely consistent with their hydrophobicity and phenobarbital eluted before secobarbital even using a phenyl-bonded stationary phase with the retention by − interaction. In CEC with NAIP [34,36], like ODS, the elution order of four barbiturates (barbital, phenobarbital, secobarbital, and thiopental) was according to their hydrophobicity (Fig.…”
Section: Separation Of Barbituratesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in CEC with ODS (Hypersil C 18 ), Euerby et al [12] demonstrated that the elution order of studied barbiturates was completely consistent with their hydrophobicity and phenobarbital eluted before secobarbital even using a phenyl-bonded stationary phase with the retention by − interaction. In CEC with NAIP [34,36], like ODS, the elution order of four barbiturates (barbital, phenobarbital, secobarbital, and thiopental) was according to their hydrophobicity (Fig.…”
Section: Separation Of Barbituratesmentioning
confidence: 99%
“…After the first report on CEC in 1974 [4], the potential of CEC has been demonstrated by a burst of outstanding separations and applications [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Since it is redundant to discuss hydrophobicity and hydrophobic selectivity in the absence of RP-temperament, as is the case with the MH OH material the reason behind the (decreased) rate of migration/retention must be sought elsewhere. Many phenomena have been associated with contributions to mechanisms occurring under CEC conditions by various authors [13,14,[33][34][35][36][37][38][39][40]. The only contributor that can be ruled out to be responsible for the observed elution of carbetocin with an increased positive κ CEC value so far is the RP-ligand.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in CEC with ODS (Hypersil C 18 ), Euerby et al demonstrated that the elution order of studied barbiturates was completely consistent with their hydrophobicity and phenobarbital eluted before secobarbital even using a phenyl-bonded stationary phase with the retention by S-S interaction [16]. In CEC with NAIP, the elution order of four barbiturates (barbital, phenobarbital, secobarbital, and thiopental) was according to their hydrophobicity ( Fig.…”
Section: Functional Stationary Phase For Cecmentioning
confidence: 97%